Ruler of Interests, Political Interests, or Law Enforcement: Case Study of Amnesty Plan for Din Minimi Group in East Aceh - Amdani, Yusi (Al-Ahkam, 2018)
The aim of this paper is the concept of the settlement of criminal cases committed Din Minimi Group. The amnesty is the prerogative of the President specified in the Constitution of 1945. Amnesty NRI is a form of pardon to political prisoners to be free from legal sanctions. The legal basis for amnesty stipulated in the Emergency Law No. 11 of 1954 on Amnesty and Abolition. The method used in this paper is a conceptual approach. Related to peace efforts in Aceh, the President has issued Presidential Decree No. 22 of 2005 on Amnesty and Abolition against GAM members. Once that happens again insurgency by Din Minimi caused dissatisfaction with the policy of the Governing of Aceh. Counterinsurgency is done by giving amnesty to the group Din Minimi so willing to surrender. When viewed in this aspect of the law, amnesty if forced to give to Din Minimi, it is destructive to the prevailing laws in Indonesia. Do not rule out the possibility of regulation will hit Indonesia polemic, so the solution had to pay attention to various aspects of both of the victim, the offender, and the community by not disregard the rule of law and justice.